(untitled) (Journal of Environmental Science and Natural Resources, 2019)
World’s populations, living in urban areas, are increasing rapidly. Rapid urbanization is placing enormous demand on urban food supply systems and causing problems like rapid decrease in green space and increase in heat island effects in urban areas. Rooftop vegetable production can reduce the temperature of roofs and the surrounding air, help to lessen urban heat island effect, can absorb carbon and noise. In some urban rooftop gardens mineral fertilizers and pesticides are used. Researchers observed that compost can be used as a source of nutrient instead of mineral fertilizers. Moreover, it can control pest, weed and diseases; reduce soil erosion; and increase soil moisture content. As kitchen wastes are common in every household in urban areas, kitchen waste compost can be a good supplement in rooftop vegetable gardens. In Bangladesh the rooftop gardening is a quite new phenomenon. This review work will help to understand rooftop gardening and to conduct future research work on rooftop gardens. J. Environ. Sci. & Natural Resources, 11(1-2): 253-259 2018